Redescription of larva of the South African endemic dobsonfly genus Chloroniella Esben-Petersen, 1924 (Megaloptera, Corydalidae), with a proposed terminology for Corydalidae larval sclerites - Martins, Caleb Califre; Contreras-Ramos, Atilano (Zootaxa, 2020)
Chloroniella Esben-Petersen is a relict, monotypic genus of Corydalidae (Megaloptera), considered sister to the remaining dobsonfly genera (Corydalinae); it is the only genus of Corydalinae known from the Afrotropical region. The larva of its only species, C. peryngueyi Esben-Petersen, 1924, was originally described by Barnard in 1931. Herein we redescribe the larva of C. peryngueyi using Scanning Electron Microscopy (SEM), colored focus-stacked images, and drawings in order to provide greater morphological detail of this significant species. Also, we propose a standardized terminology for Corydalidae larval sclerites.